Meibomian Glands and Tear Film Findings in Type 2 Diabetic Patients: A Cross-Sectional Study - Huping Wu; Huping Wu; Huping Wu; Xie Fang; Xie Fang; Shunrong Luo; Shunrong Luo; Xumin Shang; Xumin Shang; Zhiwen Xie; Zhiwen Xie; Nuo Dong; et al. (Frontiers in Medicine, 2022)
BackgroundThe characteristics of the meibomian gland and tear film in patients with type 2 diabetes (T2D) with different glycemic control levels and diabetic durations remain largely unexplored. This study aimed to identify the association of dry eye and meibomian gland dysfunction (MGD) in T2D.Materials and MethodsNinety-nine patients with type 2 diabetes mellitus (DM group), 33 dry eye patients without diabetes mellitus (DE group), and 40 normal subjects (NC group) were recruited for this study. Participants were evaluated with an Ocular Surface Disease Index (OSDI) questionnaire, tear film breakup time (BUT), the Schirmer I test (SIT), corneal fluorescein staining (FL), lipid layer thickness (LLT), and MGD parameters. Glycosylated hemoglobin (HbA1c) and duration of diabetes were recorded.ResultsThe SIT value in the DM group was higher than that of the DE group (p < 0.05). The BUT and LLT were lower, and MGD parameters were higher in the DM group than those of the DE and NC groups (p < 0.05). In the DM group, 47 patients were diagnosed with dry eye (DM + DE group), whereas 40 patients without dry eye were categorized as the DM − DE group. The SIT, BUT, and LLT values in the DM − DE group were higher (p < 0.01), and MGD parameters were lower (p < 0.01) in the DM − DE group than those of the DM + DE group. The MGD parameters were higher in the DM − DE group than those in the NC group (p < 0.05). The HbA1c levels were correlated with OSDI, BUT, LLT, FL, and MGD parameters (p < 0.001) in the DM group. However, in patients with low HbA1c, normal SIT value, and low OSDI, the MGD parameters were higher than those in the NC group (p < 0.05). The duration of diabetes positively correlated with MGD parameters (p < 0.001).ConclusionAsymptomatic MGD may be an early sign of dry eye and ocular discomfort in T2D. The MGD parameters were associated with the HbA1c level and diabetic duration.